Callus Derived Regeneration of Some Selected Brassica Genotypes (The Agriculturists, 2018)
The experiment was conducted to observe the callus induction ability of Brassica species. Plantlets were regenerated from cotyledon and stem explants of Brassica napus, Brassica campestris and Brassica juncea through direct organogenesis. The experiments were conducted in a Completely Randomized Design (CRD) with 4 replications. The highest frequency of callus formation was recorded in MS containing 2.0 mgl-1 BAP, 0.5 mgl-1 NAA and 2.0 mgl-1 AgNO3 in both stem and cotyledon explants. Among these explants, stem was found to be better responsive in callus induction than cotyledon. Among the genotypes used, BINA Sarisha-4 induced the highest percentage (100.00%) of callus from stem explants which was followed by BINA Sarisha-5 (100.00%) and Sampad (83.35%). On the other hand, BINA Sarisha-4 induced callus from 91.67% cotyledon explants, followed by BINA Sarisha-5 (75.00%) and Sampad (66.67%). Similarly, the highest percentage of shoot regeneration (58.34%) from stem explants of BINA Sarisha-4 was observed in MS medium supplemented with combination of hormone and silver nitrate concentrations. The highest percentage of root induction was 66.67 and 58.33% in plantlets derived from stem and cotyledon explants, respectively in ½ MS medium supplemented with 2.0 mgl-1 IBA and 0.5 mgl-1 of NAA. The highest survival rate was found after acclimatization of plants derived from stem (77.78%) and cotyledon (64.28%) explants of BINA Sarisha-4 in pot and 64.33 and 55.55%, respectively in field.The Agriculturists 2017; 15(2) 01-10